Wildlife conservation in Bornean timber concessions - Meijaard, E.; Sheil, Douglas; Nasi, Robert; Stanley, S.E. (2006)
Based on an extensive review of the literature, and broad consultation with experts, we have assessed the sensitivity of Bornean vertebrates to the direct and indirect effects of timber harvest. Well-implemented selective logging has a relatively limited direct impact on wildlife populations: few species appear quite sensitive, some benefit, some decline. However, current management practices in Indonesian Borneo generally cause a decline in wildlife populations. Guidelines for sustainable forest management are primarily focused on trees, with few specific recommendations on how to sustainably manage wildlife populations in timber concessions. Based on our findings, we provide extensive wildlife management guidelines, pointing out the importance of maintaining understory vegetation and large trees for fruit, seed, dead wood, and tree hollow production, limiting canopy gaps, and reducing hunting and wildlife trade in concessions. In addition, we provide specific management advice on high priority species of Bornean vertebrates.